CEREMONY OF "NYADAR" ON THE PINGGIR PAPAS SUMENEP REGENCY FROM THE ’URF PERSPECTIVE - Wafirah, Athifatul; Musyafa’ah, Nur Lailatul; Syafaq, Hammis (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Nyadar ceremony on the Pinggir Papas, Sumenep Regency is a custom as a form of respect for the services of ancestors, especially Anggasuto as the first salt discoverer in the village. This article examines how the nyadar tradition in Pinggir Papas Sumenep Regency is viewed from the perspective of urf. This research is field research that is analyzed descriptively. Data were collected through observation, interviews, and documentation. This study concluded that the awareness ceremony in Pinggir Papas Sumenep Regency was carried out 3 times a year, namely in July, August, and September. This traditional of nyadar is still influenced by Hinduism practices, such as having to prepare tajin (porridge) consisting of five colors, namely white, red, green, black, and yellow, and also offerings in the form of five rice tumpeng placed on a plate. This is the embodiment of nature which includes three dimensions, namely the lower realm, the upper realm, and the intermediate realm. The majority of people on the Pinggir Papas are Muslims and they consider that this Nyadar ceremony is not to be associated with Allah SWT. This is a form of their gratitude for the abundant salt found by Anggasuto. From the perspective of urf, the traditions of Nyadar ceremonies is in accordance tto urf shahih.